Defining the Hook Region Anatomy of the Guinea Pig Cochlea for Modeling of Inner Ear Surgery. Issue 6 (July 2017) - Lo, Jonathon; Sale, Phillip; Wijewickrema, Sudanthi; Campbell, Luke; Eastwood, Hayden; O'leary, Stephen John
Abstract : Hypothesis: The aim of this study was to describe the hook region anatomy of the guinea pig cochlea to identify the optimal surgical approach for cochlear implantation and to determine what anatomical structures are at risk. Background: Animal studies investigating hearing loss after cochlear implantation surgery are currently constrained by the lack of a reproducible implantation model. Methods: Guinea pig cochleae were imaged using thin-sheet laser imaging microscopy. Images were stitched, reconstructed, and segmented for analysis. Insertion vectors were determined by tracing their paths to the outer wall and converting to Cartesian coordinates. Spherical surface and multiplane views were generated to analyze outer wall and radial forces of the insertion vector. Results: Thin-sheet laser imaging microscopy enabled quantitative, whole specimen analysis of the soft and bony tissue relationships of the complex cochlear hook region in any desired plane without loss of image quality. Round window or cochleostomy approaches in the anteroinferior plane avoided direct damage to cochlear structures. Cochleostomy approach had large interindividual variability of angular depth and outer wall forces but predictable radial force. Conclusion: The guinea pig hook region and lower basal turn have similar structural relationships to humans. Careful cochleostomy placement is essentially for minimizing cochlear trauma and for ensuring a straight insertion vector that successfully advances around the outer wall. Experiments with guinea pigs that control for the surgical approach are likely to provide useful insights into the aetiology and the development of therapies directed at postimplantation hearing loss.